PENGARUH KEPEMILIKAN MANAJERIALTERHADAP NILAI PERUSAHAAN DENGAN SUSTAINABILITY REPORTING SEBAGAI PEMEDIASI - Sherina Winardi; Fransiskus E. Daromes; Paulus Tangke (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
This research aims to investigate the influence of managerial ownership on firm value, tested both directly and through the mediation of sustainability reporting. The theoretical basis used in building the research model is the stakeholder theory and agency theory. The population used consists of manufacturing and mining sector companies listed on the Indonesia Stock Exchange (IDX) for the research period of 2019-2021. The sample size is 15 companies each year selected using purposive sampling method and utilizing secondary data, namely annual reports and sustainability reports. The analysis method used is path analysis, and the mediation hypothesis testing is conducted using the Sobel test. The analysis results show that managerial ownership has a positive and significant effect on sustainability reporting. Managerial ownership and sustainability reporting have a positive and significant impact on firm value. This study also demonstrates how management ownership's impact on firm value is mediated by sustainability reporting.